1986
DOI: 10.1002/app.1986.070310201
|View full text |Cite
|
Sign up to set email alerts
|

New aspects in cationization of lignocellulose materials. III. Influence of delignification on reactivity and extractability of TMAHP–hemicelluloses

Abstract: SynopsisBeech sawdust samples with different lignin content were alkylated with 3chloro-2-hydroxypropyltrimethylammoniumchloride (CHMAC). The yields and the degree of substitution of trimethylammonium-2-hydroxypropyl (TMAHP) samples were similar. Differences were found in extractability of hemicelluloses from this materials both with water and dilute alkali. To obtain the maximum yield of TMAHP-hemicelluloses (ca. 90% of the amount originally present), it is sufficient to remove about 50% of lignin. The lignin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Since lignin created a network across the cell wall surface, Antal et al (1984b) found the quaternization reaction with cellulose to be hindered. Moreover, Ebringerova et al (1986) also indicated that the delignification of lignocellulosic byproducts would increase reaction efficiency with CHMAC. These findings were corroborated by Orlando et al (2002b) who could not correlate anion exchange capacity with a-cellulose content in the quaternization of six agricultural by-products with epichlorohydrin and dimethylamine.…”
Section: Resultsmentioning
confidence: 96%
“…Since lignin created a network across the cell wall surface, Antal et al (1984b) found the quaternization reaction with cellulose to be hindered. Moreover, Ebringerova et al (1986) also indicated that the delignification of lignocellulosic byproducts would increase reaction efficiency with CHMAC. These findings were corroborated by Orlando et al (2002b) who could not correlate anion exchange capacity with a-cellulose content in the quaternization of six agricultural by-products with epichlorohydrin and dimethylamine.…”
Section: Resultsmentioning
confidence: 96%
“…Since lignin created a network across the cell wall surface, the reaction between N-(3-chloro-2-hydroxypropyl) trimethylammonium chloride and cellulose was hindered. Ebringerova et al 6 indicated that lignin also influences the distribution of functional groups after reaction with N-(3-chloro-2-hydroxypropyl) trimethylammonium chloride, but does not influence the reactivity of hemicellulose, unlike cellulose.…”
Section: Introductionmentioning
confidence: 98%
“…[4] Regarding chemically modified products, the cationic 2-hydroxypropyltrimethylammonium (HPMA) xylan is well studied. [5][6][7] The synthesis was carried out in alkaline medium with 3-chloro-2-hydroxypropyltrimethylammonium chloride. Dependent on the molar ratio of xylan to reagent and of reagent to NaOH, derivatives with different degree of substitution (DS) up to 0.98 were obtained.…”
Section: Introductionmentioning
confidence: 99%